PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR PEMERINTAH (Suatu Studi Di Kecamatan Tompaso Kabupaten Minahasa) - ARING, BRIAN; Posumah, Johnny Hanny; Mambo, Rully (Sam Ratulangi University, 2016)
ABSTRACT:This research intent to know organisational culture influence to commanding apparatusperformance.. culture organisationaling to constitute one system meaning with which followed bymembered one differentiates an organization with organisational other. Performance is level success inachieving aim. Said by success if to the effect attained appropriate one is wanted. Respondentcommanding apparatus to increase performance, since performance or organisational memberedindividual achievements really determine performance organization. Therefore, performance estimationconstitutes one of essential activity instead of human resource management in organisationalObservational method that writer utilizes on this research is quantitative observational method, Withproblem formula.â€ in as much as which is influence culturizes organization to commanding apparatusperformance at tompaso district. Of analisis result product moment correlation and simple regression,can test hypothesis that declares for that â€ influential organisational Culture to commanding apparatusperformance at Tompaso district Minahasa Regency â€, on signifikansi level 1 %, It betokens thatorganisational culture so ascendant to commanding apparatus performance, notably at Tompaso district.Its outgrows affecting that gets to be observed from analisis's result determinant, whereaboutsdeterminant coefficient is gotten as big as 0,894 one get to be interpretted that outgrows it factorinfluence culturizes organization to commanding apparatus performance as big as 89,4%. This resultbetokens that performances changed variation apparatus commanding average as big as 41.79 or 69.65%prescribed by factor change variations culturize organizations as big as 89,4 %, meanwhile its rest asbig as 10.6 % regarded by factors any other.analisis result data points out that among organization culture with performance apparatusingto have relevance and influence relationship that kontributif character and so reality or signifikan.Key word: organization culture,Commanding apparatus performance ).